2019
DOI: 10.1002/jppr.1619
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of expanded practice in rural community pharmacy

Abstract: AimThe aim of this study was to identify published evidence to inform the development of expanded practice services in rural community pharmacies.Data sourcesThe search strategy was applied to the following electronic databases: MEDLINE, CINAHL, Emcare, Cochrane and Google Scholar.Study selectionIn all, 508 studies were evaluated against inclusion and exclusion criteria, with 29 eligible studies finally included in the review. Services provided needed to meet the described definition of ‘expanded practice’ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…[7][8][9] Internationally, rural pharmacists are achieving these outcomes by expanding their role in service delivery to address health needs in rural locations, including services such as disease screening, chronic disease clinics, and point-of-care testing. 10 Positive patient outcomes have been reported from the evaluation of these services. Outcomes reported have included a 20% reduction in cardiovascular risk; faster identification and management of infectious diseases including malaria, Human Immunodeficiency Virus (HIV), respiratory and urinary tract infections (RTIs, UTIs); and significantly improved management of chronic diseases including asthma, chronic obstructive pulmonary disease (COPD), cardiovascular disease, depression, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Internationally, rural pharmacists are achieving these outcomes by expanding their role in service delivery to address health needs in rural locations, including services such as disease screening, chronic disease clinics, and point-of-care testing. 10 Positive patient outcomes have been reported from the evaluation of these services. Outcomes reported have included a 20% reduction in cardiovascular risk; faster identification and management of infectious diseases including malaria, Human Immunodeficiency Virus (HIV), respiratory and urinary tract infections (RTIs, UTIs); and significantly improved management of chronic diseases including asthma, chronic obstructive pulmonary disease (COPD), cardiovascular disease, depression, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Expanded pharmacy services are evolving internationally and the potential benefits for rural and remote communities in Australia have been highlighted. [ 14 ] This study has demonstrated both supportive and opposing viewpoints, with significant differences in responses found for occupation, gender and rurality variables. Interest in pharmacists providing expanded services including sexually transmitted disease testing, vaccinations, diabetes and asthma management were found.…”
Section: Discussionmentioning
confidence: 76%
“…Rural pharmacists in Australia are widely recognised as the most accessible healthcare provider with the potential to deliver a much greater role in the health system [ 8 ]. This is common across many countries including Canada and New Zealand that share similar rural issues including a lack of access to health professionals working across vast distances and the consequent emergence of health professionals working to their full scope of practice [ 10 ]. The development of expanded services provided by rural pharmacists internationally is demonstrating small but positive impacts on health outcomes in rural and remote communities [ 10 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various prescribing models including, adapting a prescription and initiating/managing drug therapy have been implemented internationally [ 2 ]. In addition, rural community pharmacists worldwide have been trialling and providing expanded services, which include point-of-care testing for chronic disease management (e.g., HbA1c/cholesterol/spirometry), infectious diseases (e.g., malaria/HIV), disease screening, immunisation and mental health management [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation